The Level Of Student’s Statistical Reasoning In Solving Statistics Problems Based on Gender Difference - Imam Setiadi Putra ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2022)
This study aims to determine the level of students' statistical reasoning. This research was conducted in one of the schools in Donggo District, Bima Regency, NTB Indonesia by taking a sample of 2 students, namely 1 male student and 1 female student. This research is a descriptive qualitative research. Data collection techniques in this study were observation and interviews, while the instruments used were tests and interviews. The test consists of two, namely a test to determine students' mathematical abilities and a test to determine students' reasoning abilities. The results of this study indicate that the level of statistical reasoning of male students is included in the level 5 category because they have done all stages of statistical reasoning correctly, while female students are included in the level 4 category, because female students are not capable of representing the data stage.